The effect of three different training programs in elderly women’s isokinetic strength - Monteiro, António M (2020)
This study aimed was to assess the effects of three different training protocols in quadriceps and hamstrings isokinetic muscle strength of independent elderly women. Eighty women were recruited for this study and divided into four groups of twenty subjects: the control group, the multicomponent group, the muscle power group, and the muscular resistance strength group. The isokinetic strength was measured in both lower limbs with a dynamometer at 60°/s and 180º/s. The multivariate analysis (ANOVA) and the Bonferroni test assessed the group and time effect. Significant and positive effects were observed in the time and group interaction in the power group at 180°/s and 60°/s knee flexion in the dominant (p = 0.004, respectively) and non-dominant (p = 0.046 and p = 0.041, respectively) lower limbs. The Control group had significant and negative effect on the time x group interaction at 180°/s and 60°/s on the extension of the dominant knee (p = 0.008 and p = 0.001, respectively) and non-dominant (p = 0.003 and p< 0.001, respectively). The muscle power training seems to be the most effective to increase the isokinetic strength in older independent women. All the training programs appear to contribute to decreasing the age-related loss on isokinetic strength.